Geographic Information System Based Three-Dimensional Soil Water Dynamic Model For Landslide Modelling - Reli, Siti Nurbaidzuri (2022)
The current three-dimensional (3D) geospatial model neglects the importance of dynamic changes and focuses more on static modelling. By emphasizing the dynamism of 3D geospatial landslides triggered by soil water movement, this study aims to develop a three-dimensional Soil Water Dynamic Flow (3D SWD FLOW) model to represent an effectual movement and mitigate the severe implications of landslide hazards using a novel Danger Level (DL) approach.